Developing Green Infrastructure: Management of Madrasah Building Construction with Green Building Principles - M. Munir; Akhmat Fanani Ridho; Juni Iswanto; M. Burhanuddin Ubaidillah; Toha Ma'sum; Syaiful Muda'i; Niken Ristianah (Journal of Golden Generation Multidisciplinary, 2025)
This study examines the management processes involved in developing green infrastructure for Islamic educational institutions, specifically focusing on the construction of madrasah buildings using green building concepts. It investigates how environmental sustainability principles can be systematically integrated into the planning, design, construction, and operational phases of madrasah development projects. Utilizing a qualitative case study approach combined with document analysis, this research analyzes two madrasah building projects in Indonesia that have implemented green building strategies. Data were collected through in-depth interviews with project managers, architects, contractors, madrasah leaders, and stakeholders, alongside analysis of project documents, designs, and specifications. Findings reveal that successful implementation requires an integrated management approach encompassing green design adaptation to local context, sustainable material sourcing, energy and water efficiency integration, waste management during construction, and life-cycle cost considerations. The study identifies key enablers including leadership commitment, technical expertise, community participation, and Islamic ethical alignment, while highlighting challenges such as budget constraints, regulatory gaps, and technical capacity limitations. This research contributes a framework for madrasah green building project management that balances environmental responsibility with educational functionality and Islamic architectural values.